Analisis Pola Pembangunan Perekonomian Mandiri Pondok Pesantren ( Studi Kasus Pondok Pesantren Baitul Qurro’ Wal Huffazh Kerongkong) - fahurrazak; Hikmatul Hidayati MZ; Arpian Lutfi (Al-Qardhu, 2025)
This research is motivated by the importance of the role of Islamic boarding schools in shaping economic independence in the community. The Baitul Qurro' Wal Huffazh Islamic boarding school in East Lombok is an example of an Islamic educational institution that not only focuses on religious education, but also develops the economic sector through various business units. This change aims to improve the quality of pesantren education as well as provide entrepreneurial provisions to students so that they can be economically independent. With this pattern, pesantren is expected to make a positive contribution to the surrounding community. The research method used is field research with a social anthropology approach. The data analysis technique used is qualitative descriptive, data obtained through observation, interviews, and documentation carried out directly at the Baitul Qurro' Wal Huffazh Islamic Boarding School. The researcher focuses on the pattern of independent economic development, the role of the community, and the resulting economic impact. The research subjects involved pesantren administrators, students, and the surrounding community. Data analysis techniques include data collection, reduction, presentation, and conclusion drawing to understand phenomena holistically. The results of the study show that pesantren has developed business units such as agriculture, livestock, and pesantren cooperatives that are managed with students. This activity not only supports the operation of the pesantren but also improves the skills of students in entrepreneurship. Despite facing challenges such as limited capital and lack of understanding of management, this independent economic venture provides great benefits in creating an independent and competitive Islamic boarding school, as well as having a positive economic impact on the surrounding community.